THE IMPACT OF CORPORATE GOVERNANCE MECHANISM ON FIRM FINANCIAL PERFORMANCE: EVIDENCE FROM THE UK - Odom, Ethel Ohanya (2012)
This study examines the relationship between corporate governance mechanism and firm performance. Six (6) corporate governance mechanisms were considered in a sample of 53 FTSE 100 firms listed on the London Stock Exchange from 2008 to 2011. The mechanisms are; board size, board composition, board leadership, Board activity (frequency of board meetings), board committee (audit, remuneration and nominations) composition and frequency of meetings and ownership concentration. Using Ordinary Least Square (OLS) and fixed effects regression, the findings did not show any relationship between board size, ownership concentration (a significant negative relationship with Tobin’s Q with fixed effects regression), 100% NED audit committee, remuneration committee composition, frequency of audit and remuneration committee chairman CEO duality and firm performance. Contrary to expectation that increased outside representation on the board will increase performance (Fama and Jensen, 1993), the results show a significant negative relationship between board composition and firm performance. The results also show a negative relationship between board activity and performance. Similarly, a significant negative relationship between nomination committee comprising only NEDS and performance was also shown by my results. The findings of this study suggests that more than just structural compliance with corporate governance codes is required for a positive effect on performance, and also that governance variables are endogenous to firm performance.